Invitations and Incentives : A Qualitative Study of Behavioral Nudges for Primary Care Screenings in Armenia - Gong, Estelle (Springer Nature, 2021)
Non-communicable diseases account for a growing proportion of deaths in Armenia, which require early detection to achieve disease control and prevent complications. To increase rates of screening, demand-side interventions of personalized invitations, descriptive social norms, labeled cash transfers, and conditional cash transfers were tested in a field experiment. Our complementary qualitative study explores factors leading to the decision to attend screening and following through with that decision, and experiences with different intervention components. An individual’s decision to screen depends on 1) the perceived need for screening based on how they value their own health and perceive hypertension and diabetes as a harmful but manageable condition, and 2) the perceived utility of a facility-based screening, and whether screening will provide useful information on disease status or care management and is socially acceptable. Following through with the decision to screen depends on their knowledge of and ability to attend screenings, as well as any external motivators such as an invitation or financial incentive. Personalized invitations from physicians can prompt individuals to reconsider their need for screening and can, along with financial incentives, motivate individuals to follow through with the decision to screen. The effect of descriptive social norms in invitations should be further studied. Efforts to increase preventive screenings as an entry point into primary care in Armenia may benefit from implementation of tailored messages and financial incentives.